2000
DOI: 10.1088/0965-0393/8/3/317
|View full text |Cite
|
Sign up to set email alerts
|

Structure and energetics of Cu-Au alloys

Abstract: The structures and energetics of Cu-Au alloys over a wide range of temperatures are studied using a combination of quasi-harmonic (QH) lattice dynamics and Monte Carlo (MC) simulations at constant temperature and constant pressure. The many-body potential used is fitted to room-temperature experimental data taking vibrational contributions into account. Transitions to the disordered phases are studied using MC simulations in which not only anisotropic deformation of the unit cell and atomic movements are allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…Experimental investigation of ordered Cu-Pt alloys have shown that twin formation can occur in{111}〈 〉 slip system [103], butalloys preferfull dislocation emission as is generally in ordered M. Muzyk [47] *Experimental data structures [49]. Au: Cu-Al alloys form ordered structures [104]. Volkov has found high strength and ductility of ordered Cu-Au alloys, the highest mechanical properties of an equiatomic Cu-Au alloy can be obtained if its structure is refined as much as possible.…”
Section: Stacking Fault Energies In Copper In 5d Transition Metal Alloysmentioning
confidence: 99%
“…Experimental investigation of ordered Cu-Pt alloys have shown that twin formation can occur in{111}〈 〉 slip system [103], butalloys preferfull dislocation emission as is generally in ordered M. Muzyk [47] *Experimental data structures [49]. Au: Cu-Al alloys form ordered structures [104]. Volkov has found high strength and ductility of ordered Cu-Au alloys, the highest mechanical properties of an equiatomic Cu-Au alloy can be obtained if its structure is refined as much as possible.…”
Section: Stacking Fault Energies In Copper In 5d Transition Metal Alloysmentioning
confidence: 99%
“…The discrepancy between the results of the theory and experiment is mostly due to the fact that the EAM potential model of Ref. 23 is not quite accurate to reproduce the experimental melting temperature T m = 1336 K of pure Au ͑see Fig. 5͒.…”
Section: ͑12͒mentioning
confidence: 92%
“…In the present paper this methodology is applied to study the freezing of liquid Au-Cu alloy with an embedded atom model ͑EAM͒. 23 In general, EAM model potentials are widely used to describe many properties of metals and alloys. 24,25 These potentials have a density-dependent term, which includes many-body interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Barrera put forward an EAM model for Au-Cu alloys [19], which was fitted to room-temperature experimental data and took vibrational contributions into account. This model has been applied successfully to describe the characteristics of the order-disorder transition and the structures and cohesive energies of Au-Cu alloys.…”
Section: Inter-atomic Potentialmentioning
confidence: 99%